CANINE PARVOVIRUS INFECTION IN A LOCAL PUPPY FROM SEMPIDI VILLAGE, BADUNG REGENCY: A CASE REPORT - Yurika, Luh Putu Vivin; Kencana, Gusti Ayu Yuniati; Suarjana, I Gusti Ketut; Kardena, I Made; Oka, Ida Bagus Made (Buletin Veteriner Udayana, 2026)
Canine parvovirus (CPV) is a highly contagious viral disease associated with high mortality rates in dogs, particularly in puppies. Clinically, CPV infection manifests in two forms: enteritis and myocarditis. The virus spreads rapidly among dogs through direct contact with infected animals or indirect contact with contaminated feces and fomites. This case report describes a local male dog, approximately two months of age, from Sempidi Village, Mengwi District, Badung Regency, Bali, that presented with lethargy, anorexia, vomiting, refusal to eat and drink, and bloody diarrhea. Gross pathological examination revealed cerebral vascular congestion and meningeal hyperemia, cardiomegaly, multifocal pulmonary discoloration, multifocal discoloration of the liver lobes, dark discoloration of the renal cortex and medulla, splenomegaly, and hemorrhages affecting both the intestinal serosa and mucosa. Histopathological examination demonstrated meningoencephalitis, edematous necrotizing myocarditis, necrohemorrhagic bronchopneumonia, hemorrhagic hepatitis, hemorrhagic splenitis, necrohemorrhagic glomerulonephritis, and necrotizing enteritis. Polymerase chain reaction (PCR) testing confirmed CPV infection. Based on the anamnesis, clinical presentation, epidemiological findings, gross and histopathological lesions, and molecular diagnostic results, the dog was diagnosed with canine parvovirus infection.